Penetration testing with Raspberry Pi learn the art of building a low-cost, portable hacking arsenal using Raspberry Pi 3 and Kali Linux 2.: learn the art of building a low-cost, portable hacking arsenal using Raspberry Pi 3 and Kali Linux 2. (November 2016) - McPhee, Michael; Beltrame, Jason
No abstract available